Trans-germanic peculiarities of preterite-present verbs - Botsman , Andriy; Dmytruk , Olga (Current issues of Ukrainian linguistics: theory and practice, 2020)
This article contains systematic and detailed analysis of morphological and semantic parameters of Germanic preterite-present verbs, dividing them into major and minor subgroups. The development of both preterite-present subgroups and their steady transformation into the modal verbs is a specific feature of all Germanic languages. Since the modal verbs of the Modern Germanic languages are morphologically defective, it is commonly assumed that preterite-present verbs of the old Germanic languages lost some of their morphological features in the process of turning into modal verbs. The semantic aspects of this process are rather obscure. All Germanic languages were losing some preterite-present verbs in the process of transformation from the Gothic language, which had fourteen preterite-present verbs. In OE there were twelve preterite-present verbs. Six of them survived in NE. The morphological description  focuses on the finite and non-finite forms of the preterite-present verbs, which belong to the minor subgroup. The detailed description helps to see the origin and development of the minor subgroup in the new light. The description encompasses the data of classical Indo-European languages and Old Germanic languages. The authors emphasize the expediency of turning to the theory of preterite/strong verb origin, the verbs in question may be regarded as inter-group, hybrid units. In order to gain insight into the origin of the Germanic languages it is necessary to look into the history of the Gothic and West Germanic and North Germanic languages. The authors find it useful to compare common and different phenomena, highlighting individual specific processes taking place in the process of development of the Germanic languages. These languages are analyzed on different stages of their development, but inline with the view that the languages co-operated and coexisted in the same area. The data given in the article are used to analyze the problem implementing comparative grammar tools. The authors were particularly careful to take all grammatical forms into consideration while working with the lexical units from the ancient sources. Some additional information was taken from Greek, Latin and Sanskrit to produce reliable and consistent comparison of the German language with the rest of Indo-European languages.
Keywords: preterite-present verbs, Germanic languages, Common Germanic roots, semantic derivation, grammatical cooperation.